THE WEEK IN HIGHER EDUCATION. (Times Higher Education, 2011)
This section offers news briefs on higher education in Great Britain as of December 2011. The leak of a second batch of emails stolen from the Climatic Research Unit at the University of East Anglia failed to reignite the Climategate controversy. Historian Niall Ferguson warned Indian author Pankaj Mishra that he will sue him for libel if he did not apologize for calling him a racist. Campaigners welcomed the announcement of additional science funding to boost investment for research councils.